2009
DOI: 10.1136/bmj.b3914
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and cardiovascular disease: systematic review and meta-analysis

Abstract: Objective To evaluate the association between migraine and cardiovascular disease, including stroke, myocardial infarction, and death due to cardiovascular disease. Design Systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
646
12
26

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 706 publications
(712 citation statements)
references
References 29 publications
21
646
12
26
Order By: Relevance
“…Pre-eclampsia is itself associated with pre-term birth, perinatal death 3 and with infant stroke in the perinatal period, 24 and also with risk of maternal pregnancy-associated stroke 7 and with long-term stroke risk in the mother. 4 In preeclampsia, 25,26 as in migraine, 27,28 there are features of endothelial dysfunction, platelet activation and inflammation.…”
Section: Migraine and Preterm Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-eclampsia is itself associated with pre-term birth, perinatal death 3 and with infant stroke in the perinatal period, 24 and also with risk of maternal pregnancy-associated stroke 7 and with long-term stroke risk in the mother. 4 In preeclampsia, 25,26 as in migraine, 27,28 there are features of endothelial dysfunction, platelet activation and inflammation.…”
Section: Migraine and Preterm Birthmentioning
confidence: 99%
“…Other indications that factors relevant to reproductive function interact with propensity to migraine are the concentration in some women of migraine headaches at the time of menstrual periods and the commonly observed decline of migraine attacks during pregnancy or after menopause. 3 Ischemic stroke is more common in women with than without migraine, 4,5 and risk is increased in those taking oral contraceptives. 6 There is a striking increase in frequency of pregnancy-associated stroke in women with a history of migraine, although the absolute level of that risk is low.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features of GIDs in migraine patients are most commonly characterized by the effects of acidic gastric juice on mandibular teeth (14). Several studies have demonstrated possible relationship between cardiovascular diseases (CVDs) and migraine (4,15,16). The functional significance of CVDs in migraine patients is that poor oral hygiene could be a predisposing factor for infective endocarditis caused by streptococcal bacteria (17).…”
Section: Introductionmentioning
confidence: 99%
“…This disorder is most commonly experienced between the ages of 15 and 55 years, and 70% to 80% of sufferers have a family history of migraine (3). A widely accepted neurovascular theory of migraine etiology consists of dural and meningeal vascular dilatation, perivascular inflammation, and nociceptor activation (4). The reflection of migraine pain to the temporomandibular, facial, and maxillary areas has been ascribed to vascular dilatation and inflammation of the trigeminal nerve, which emanates from the brainstem and innervates the orofacial area (5).…”
Section: Introductionmentioning
confidence: 99%
“…Since the available evidence on the topic increased considerably over the past years, a recently published me-ta-analyses sought to assess the current evidence on the association between migraine and various CVD events, including stroke subtypes, angina, myocardial infarction (MI), and CVD death 52 (Table 2). Studies were heterogeneous with regard to the characteristics of investigated subjects and definition of cardiovascular events.…”
Section: Summarizing the Evidencementioning
confidence: 99%